Simulation of Solar Panel Design as an Energy Source for Catfish Ponds - Maulana, Ade Putra; Duli, Sirlus Andreanto Jasman; Istoto, Enggar Hero; Peprizal, Peprizal; Faristasari, Evvin (Journal of Technology and Engineering, 2025)
The increasing demand for sustainable energy solutions has driven the adoption of solar photovoltaic (PV) systems in various industries, including aquaculture. This study designs and simulates a solar power system for small-scale catfish (Lele) pond operations using the System Advisor Model (SAM). The methodology includes assessing energy requirements, selecting system components, conducting simulations, and performing an economic feasibility analysis. The results indicate that the designed 12-panel, 3-battery solar system effectively meets the pond’s daily energy demand while ensuring continuous operation during low sunlight conditions. The SAM simulation confirms stable electricity generation throughout the year, with seasonal variations minimally affecting efficiency. The economic analysis reveals that PLTS costs Rp. 150,365 per month, compared to Rp. 151,620 for PLN electricity, showing small but valuable long-term savings. Despite the high initial investment, solar power offers price stability, energy independence, and reduced reliance on fossil fuels. This study demonstrates that solar energy is a viable, cost-effective, and sustainable alternative for aquaculture operations. Future research should focus on optimizing system efficiency and integrating hybrid energy solutions to further enhance performance and financial benefits.